(untitled) (Research, Society and Development, 2022)
In women’s health, physiotherapy has been gaining more and more space in clinical practice, and one of the also important areas is urogynecological physiotherapy, which aims to prevent and treat disorders related to the pelvic floor muscles. Physiotherapeutic treatment to strengthen the pelvic floor muscles is essential, since when they are weakened, several consequences can be observed, one of which is genital prolapse, which is a pathology that generates instability of the bladder and pelvic organs. Therefore, the present study aims to analyze the importance of strengthening the pelvic floor muscles in the prevention of genital prolapse, addressing physical therapy interventions such as biofeedback, electrostimulation, vaginal cones and kinesiotherapy exercises. This is a descriptive and quantitative bibliographic review, based on scientific articles published in the last 10 years, indexed in the main databases focused on the health area (Scielo, PubMed and Lilacs), materials obtained during graduation and books. To search for studies, the following health descriptors (DECs) were used: “pelvic floor”, “pregnancy” “pelvic prolapse”. Over the years, women face several specific periods, which are decisive for hormonal, physical and psychological changes, and a very common consequence in the female audience is the weakening of the pelvic floor muscles, thus realizing that strengthening through physical therapy is an important ally for the improvement of this clinical condition, which when aggravated can result in a great embarrassment for women. Therefore, physiotherapy acts both in the prevention and treatment of these disorders and aims to improve the strength of the pelvic floor muscles, promoting mobility gain and preventing possible changes and their consequences.